Language Choice Codes Used by Clothing Sellers and Buyers in Maisara Shop, BTC (Beteng Trade Center), Pasar Kliwon, Surakarta - Anindita, Widyashanti Kunthara; Wardani, Ni Luh Shinta Mikha (Universitas Muhammadiyah Semarang, 2018)
The research aims to describe the language choice codes used by clothing Sellers and buyers in Maisara Shop, BTC (Beteng Trade Center, Pasar Kliwon, Surakarta. This research uses the sociolinguistics approach. The data of this research are utterances of the clothing sellers and buyers in Maisara Shop, BTC. The sources of the data are the sellers and the buyers in the traditional market. The data were collected by using observation and interview methods. Then, contextual approach is used to analyze the data. This research yields the following findings such as: (1) The language codes consist of code switching and code mixing. Code switching occurs from Indonesian-Javanese and Javanese-Indonesian. Meanwhile code mixing occurs in Indonesian, Javanese and English Words; (2) The speech level code only consist of ngoko; (3) The style codes consist of elaborated and restricted codes; (4) The dialect codes consist of Pekalongan, Surakarta and Semarang dialects; (5) The register codes consists of eleven words that are only be understood by the clothing sellers.